Efektivitas Media E-Cerpen dalam Pembelajaran Membaca Cerita Anak Siswa Kelas V SD Inpres 12/79 Batugading Kecamatan Mare Kabupaten Bone - Evi Susanti Bakri; Idris, Idris; Irna Fitriana; Muh. Safar; Andi Tenris Sua (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aimed to determine the effectiveness of using E-Short Story media in teaching children’s story reading skills to fifth-grade students of SD 12/79 Batu Gading, Mare District. The research employed a quasi-experimental method with a one-group pretest–posttest design. The research subjects consisted of 32 fifth-grade students. The instrument used was a reading comprehension test administered before and after the implementation of the E-Short Story media. The data were analyzed using descriptive statistics and a t-test to identify differences in students’ learning outcomes before and after the treatment. The results showed an improvement in students’ ability to read and understand children’s stories after the use of E-Short Story media. The mean posttest score was higher than the mean pretest score, indicating that the E-Short Story media was effective in improving reading skills. The use of E-Short Story media also increased students’ learning motivation, comprehension of story content, and active participation in the learning process. Therefore, E-Short Story media is recommended as an alternative learning medium for teaching reading in elementary schools.